The New European Bauhaus: Beautiful-Sustainable-Together in STARHAUS - Petruț Bratu; Akhilesh Kumar Srivastava; Alex Butean; Letizia Vaccarella (Transylvanian Review of Administrative Sciences, 2024)
The article ‘The New European Bauhaus: Beautiful-Sustainable-Together in STARHAUS’ aims to explore the principles of the New European Bauhaus (NEB) policy and analyze how these principles are implemented across various European projects, with a specific focus on the STARHAUS project. The New European Bauhaus is an interdisciplinary initiative launched by the European Commission to foster a sustainable and inclusive future by combining aesthetics, sustainability, and inclusiveness. It seeks to create spaces, products, and services that are environmentally friendly, inclusive, and accessible while enhancing quality of life.